2020
DOI: 10.1172/jci141206
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma anti–SARS-CoV-2 spike protein ectodomain and receptor-binding domain IgG correlate with virus neutralization

Abstract: The newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) highlights the urgent need for assays that detect protective levels of neutralizing antibodies. We studied the relationship among anti-spike ectodomain (anti-ECD), antireceptor-binding domain (anti-RBD) IgG titers, and SARS-CoV-2 virus neutralization (VN) titers generated by 2 in vitro assays using convalescent plasma samples from 68 patients with COVID-19. We report a strong positive correlation between both plasma anti-RBD and ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
162
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 188 publications
(185 citation statements)
references
References 36 publications
20
162
2
1
Order By: Relevance
“…Notably, one study showed that 40% of convalescent patients did not have any neutralizing activity (Prevost et al, 2020), suggesting that neutralizing antibodies are not absolutely required for infection resolution. As expected, significant correlations between neutralizing activities and anti-S protein antibody titers were observed (Ni et al, 2020;Prevost et al, 2020;Salazar et al, 2020;Wu et al, 2020a). Neutralizing antibody titers were also strongly correlated with the numbers of virus-specific T cells (Ni et al, 2020), suggesting coordinated humoral and cellular immune responses.…”
Section: Structural and Neutralizing Properties Of Anti-sars-cov-2 Ansupporting
confidence: 71%
“…Notably, one study showed that 40% of convalescent patients did not have any neutralizing activity (Prevost et al, 2020), suggesting that neutralizing antibodies are not absolutely required for infection resolution. As expected, significant correlations between neutralizing activities and anti-S protein antibody titers were observed (Ni et al, 2020;Prevost et al, 2020;Salazar et al, 2020;Wu et al, 2020a). Neutralizing antibody titers were also strongly correlated with the numbers of virus-specific T cells (Ni et al, 2020), suggesting coordinated humoral and cellular immune responses.…”
Section: Structural and Neutralizing Properties Of Anti-sars-cov-2 Ansupporting
confidence: 71%
“…In addition to disease severity, we report for the first time that specific COVID-19 symptoms, namely fever, low appetite, abdominal pain, and diarrhea, consistently correlate with higher antibody titers (Table 3). Other symptoms did not correlate consistently or at all including shortness of breath, which a previous study of 68 COVID-19 convalescent subjects who donated plasma at various times post-infection found was associated with higher antibody titers (20). Fever and low appetite are signs of a systemic inflammatory response, suggesting that such an inflammatory response may be key for developing a strong anti-SARS-CoV-2 antibody response.…”
mentioning
confidence: 71%
“…Also, different methods are used to detect antibody titers, and neutralizing titers tend to be low more often than anti-SARS-CoV-2 antibody levels (20,21). Of course, small sample size is a well-known cause of variable data.…”
Section: Introductionmentioning
confidence: 99%
“… 27 Although this assay does not differentiate binding IgG antibodies from virus-neutralizing IgG antibodies, a strong correlation has been shown between the amount of antispike protein IgG and in vitro virus neutralization. 28 , 29 This IgG chemiluminescent immunoassay is a qualitative assay that is based on the detection of IgG antibodies against a recombinant form of the SARS-CoV-2 spike subunit 1 protein. Numerical results of the assay correspond to the ratio of the sample signal to a calibrator-assigned cutoff signal (the signal-to-cutoff ratio).…”
Section: Methodsmentioning
confidence: 99%